Pengaruh Struktur TArif Air Terhadap Permintaan Konsumen PDAM Way Rilau Dalam Perspektif Ekonomi Islam - Muzakky, Fata Nafis; Madnasir; Supriyaningsih, Okta (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2025)
This study examines the influence of water tariff structures on consumer demand for PDAM Way Rilau in Kemiling District, Bandar Lampung, within the perspective of Islamic economics. The research aims to analyze how progressive tariff schemes affect consumer behavior and evaluate their compliance with Islamic principles of justice (al-‘adl), welfare (maslahah), and the prohibition of harm (la dharar wa la dhirar). A qualitative descriptive method was employed, supported by surveys, interviews, observations, and documentation involving household and commercial consumers. Findings reveal that progressive block tariffs significantly shape consumption patterns: low-income households tend to restrict usage within the first block, while middle- and high-income consumers display greater tolerance to tariff increases. However, the application of a minimum charge raises concerns of fairness. The study concludes that while tariff structures partially reflect Islamic values through cross-subsidization, improvements in transparency and equity are necessary. The novelty lies in integrating Islamic economic principles into local water pricing policy evaluation.